Experiential learning activities in university accounting education: A systematic literature review. (September 2020) - Gittings, Lara; Taplin, Ross; Kerr, Rosemary
Highlights: Systematic Literature Review of benefits of ELAs for accounting undergraduates. Research gaps identified yielded five recommendations for future research. Filling these gaps will assist accounting educators and professional bodies. Abstract: There have been multiple calls for change in higher education in accounting in Australia since the 1980s. These calls for change were motivated by industry demands for graduates with transferable skills. Many universities started responding to these calls for change by introducing more Experiential Learning Activities (ELAs) into their accounting courses. This article is the first to provide a systematic review and thematically analyse the body of research published about ELAs in undergraduate accounting courses at universities. The aim is to review what types of ELAs are researched, what benefits of ELAs are researched and the strength of the evidence provided for these benefits. The 50 captured articles from 1993 to 2018 presented a positive view of ELAs, with the shortcomings far outweighed by the benefits. The most commonly researched benefits that emerged from the review were technical knowledge and comprehension, student attitude and satisfaction as well as authentic application of theory. Five recommendations for future research have been identified including investigating transferable skills as a benefit of ELAs, exploring student characteristics and ELA characteristics that can effect ELA learning outcomes, investigating under-researched benefits and using more diversified and rigorous research designs.